3. ANXIETY DISORDERS AMONG HIV/AIDS PATIENTS RECEIVING TREATMENT AT THU DUC CITY HOSPITAL AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objectives: To determine the prevalence of anxiety disorders and associated factors among HIV patients receiving treatment at Thu Duc City Hospital.Methods: A descriptive cross-sectional study was conducted on 369 HIV patients receiving treatment at Thu Duc City Hospital from March to May 2024. A convenient sampling technique, using a prepared questionnaire including the Generalized Anxiety Disorder-7 (GAD-7). The chi-square test (or Fisher's exact test) and PR were used to determine associations.Results: The prevalence of anxiety disorders in HIV patients was 29,3%. Statistically significant factors related to anxiety disorders included the time since diagnosis, economic status and side effects.Conclusion: Mental health in HIV patients receiving treatment needs more attention, especially in groups with a short time since diagnosis, economic difficulties, and side effects.
Keywords: Anxiety Disorders; HIV; GAD-7; Thu Duc City Hospital